High-strength wear-resistant concrete and preparation method thereof

By using polyether etherketone modified gravel, polyamide resin modified sand, high-strength fibers and high-strength fillers in high-strength concrete, the problems of high-strength, wear resistance and fire resistance in high-rise buildings and large-span bridges are solved, and structural stability and safety under fire conditions are achieved.

CN119797832APending Publication Date: 2025-04-11BEIJING XINJIANGFENG BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411789150.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-11
Filing Date
2024-12-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the application of high-strength buildings and large-span bridges, existing high-strength concrete is difficult to meet the requirements of high strength, wear resistance and fire resistance at the same time, especially in fire conditions, which is prone to cracking and collapse problems, affecting fire rescue and personnel evacuation.

Method used

Using a combination of polyether ether ketone modified gravel, polyamide resin modified sand, high-strength fiber and high-strength filler, the high-temperature viscosity and bonding effect of polyether ether ketone and polyamide resin is combined with the strength of high-strength fiber and high-strength filler, the strength and wear resistance of concrete are improved, and structural stability is maintained under fire conditions.

Benefits of technology

Concrete with high strength, wear resistance and fire resistance is achieved, which can maintain structural stability under fire conditions, avoid cracking and collapse, and extend the time for fire rescue and personnel evacuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174884750000111
    Figure BDA0005174884750000111
Patent Text Reader

Abstract

The invention relates to the field of concrete, and particularly discloses high-strength wear-resistant concrete and a preparation method thereof. The high-strength wear-resistant concrete is prepared from the following raw materials in parts by weight: 350 to 450 parts of cement, 150 to 180 parts of water, 50 to 80 parts of fly ash, 120 to 140 parts of mineral powder, 950 to 1100 parts of polyether-ether-ketone modified macadam, 600 to 900 parts of polyamide resin modified sand, 2 to 4 parts of water reducing agent, 20 to 30 parts of high-strength fiber and 25 to 35 parts of high-strength filler, the preparation method comprises the following steps: weighing the cement, the fly ash and the mineral powder, uniformly mixing and stirring, then adding the polyether-ether-ketone modified macadam and the polyamide resin modified sand, and uniformly mixing and stirring to obtain a primary mixture; adding high-strength fiber and high-strength filler into the primary mixture, uniformly mixing and stirring, then adding a water reducing agent and water, and uniformly mixing to obtain a mixture; and pouring and curing the mixture to obtain a finished product. The material has the advantages of high strength, wear resistance and good fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete, and more specifically, to a high-strength wear-resistant concrete and a preparation method thereof. Background Art

[0002] High-strength concrete refers to concrete with a strength of C60 or above, which is made by mixing cement, sand, gravel, fly ash, mineral powder, silica fume, water reducer and other materials; high-strength concrete has the advantages of high compressive strength, strong deformation resistance, high density and low porosity, and is widely used in high-rise buildings and large-span bridge structures.

[0003] In recent years, the problem of fire in high-rise buildings has gradually attracted people's attention, so the concrete used in high-rise buildings needs to have not only high strength, but also good fire resistance; and the long-span bridge structure needs to have not only high strength, but also good wear resistance. At the same time, fires on bridges caused by traffic accidents, and even explosions on bridges, also require the concrete used on large-span bridges to have good fire resistance; even under fire conditions, it is not easy to affect the strength of the concrete, and the concrete structure can be relatively stable and not prone to collapse, which buys time for fire rescue and personnel evacuation.

[0004] Therefore, how to prepare a concrete that is simultaneously high-strength, wear-resistant, and fire-resistant, and used in high-rise buildings and large-span bridges; even under fire conditions, it can have high strength and good stability, and is not prone to collapse or breakage, thus buying time for fire rescue and personnel evacuation. Summary of the invention

[0005] In order to prepare a concrete that is simultaneously high-strength, wear-resistant and fire-resistant, and is used in high-rise buildings and large-span bridges; even under fire conditions, it can have high strength and good stability, and is not prone to collapse and breakage, thereby buying time for fire rescue and personnel evacuation, the present application provides a high-strength wear-resistant concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-strength wear-resistant concrete, which adopts the following technical solution: A high-strength wear-resistant concrete comprises the following raw materials in parts by weight: 350-450 parts of cement, 150-180 parts of water, 50-80 parts of fly ash, 120-140 parts of mineral powder, 950-1100 parts of polyetheretherketone modified crushed stone, 600-900 parts of polyamide resin modified sand, 2-4 parts of water reducing agent, 20-30 parts of high-strength fiber and 25-35 parts of high-strength filler.

[0007] By adopting the above technical scheme, polyetheretherketone modified gravel, polyamide resin modified sand, high-strength fiber and high-strength filler are matched, and the higher strength of polyetheretherketone and polyamide resin is combined with the strength of high-strength fiber and high-strength filler to improve the strength and wear resistance of concrete.

[0008] After a fire occurs, the concrete is prone to cracking due to the loss of moisture in the concrete, especially between gravel and sand and cementitious materials. The loss of moisture causes the cementitious materials to lose their bonding strength, resulting in a decrease in the bonding effect between gravel, sand and cementitious materials.

[0009] By utilizing the high-temperature viscosity of polyetheretherketone and the high-temperature bonding effect of polyamide resin, the cementitious materials formed by crushed stone, sand and cement are closely bonded, thereby ensuring that the concrete of high-rise buildings is not prone to cracking under high-temperature fire, ensuring the structural strength of concrete, and buying more time for the evacuation and rescue of personnel; and the polyamide resin first expands slightly at high temperature and fills the pores generated by water loss in the high-strength concrete, and the polyamide resin is flexible, and its deformation can also buffer the pores inside the concrete, and then gradually melts as the temperature rises, achieving close bonding between the sand and the surrounding raw materials; as the temperature continues to rise, the polyetheretherketone on the surface of the crushed stone gradually melts, further improving the bonding effect of the crushed stone with sand, cementitious materials, high-strength fibers, high-strength fillers and other materials, and trying to avoid the generation of cracks that cause the collapse of high-rise buildings, so that even if a fire occurs in a high-strength concrete building, it can have higher strength and better stability, and is not prone to collapse or fracture, thus buying time for the evacuation and rescue of personnel.

[0010] Preferably, the polyetheretherketone modified gravel is made of gravel, rosin resin and calcium phosphate grafted polyetheretherketone in a mass ratio of 1000:2-5:5-15.

[0011] By adopting the above technical scheme, crushed stone and calcium phosphate aluminate grafted polyetheretherketone are matched, and the flexibility of polyetheretherketone is utilized to improve the strength of concrete and make the concrete less likely to crack; after a fire occurs, the flame retardant effect of calcium phosphate aluminate is utilized, and the high-temperature hot-melt viscosity of polyetheretherketone is combined to bond the crushed stone with sand, high-strength fiber, high-strength filler, and cementitious material, so that the high-strength concrete has better fire resistance and flame retardancy, and can also ensure the strength of the high-strength concrete, so that the high-strength concrete of high-rise buildings is not prone to large cracks and collapse in a fire.

[0012] Preferably, the calcium aluminophosphate grafted polyetheretherketone is made of polyetheretherketone, calcium aluminophosphate and sodium alginate solution in a mass ratio of 1:0.2-0.4:0.1-0.2.

[0013] By adopting the above technical scheme, polyetheretherketone, calcium phosphate aluminate and sodium alginate solution are matched, and the viscosity of the sodium alginate solution is used to facilitate the bonding of calcium phosphate aluminate to the surface of polyetheretherketone; and the sodium alginate solution facilitates the bonding of calcium phosphate aluminate grafted polyetheretherketone with gravel, thereby balancing the problem of poor bonding between the cementitious material and the gravel due to water loss under fire. At the same time, polyetheretherketone has good flexibility. Even after the fire is extinguished, the toughness of polyetheretherketone can ensure the strength of the concrete, and it is not easy to have the problem of overcooling or overheating to increase the cracks in the concrete, thereby ensuring the strength stability of the concrete after the fire is extinguished, and it is not easy to have the problem of collapse.

[0014] Polyetheretherketone, calcium phosphate aluminate and sodium alginate solution are combined. During the mixing process, the bonding effect of the water-soluble sodium alginate is utilized in combination with the bonding effect of the cementitious material and the carboxyl group, so that the calcium phosphate aluminate grafted polyetheretherketone and the cementitious material can be tightly bonded, thereby improving the structural strength of the high-strength concrete. Moreover, under the high temperature conditions of a fire, the sodium alginate can be carbonized to become flame retardant, and combined with the high temperature resistant flame retardant effect of polyetheretherketone, the fire resistance of the finished high-strength concrete can be further improved.

[0015] Preferably, the polyamide resin modified sand is made of river sand, rosin resin and expanded graphite grafted polyamide resin in a mass ratio of 1000:1-3:3-8.

[0016] By adopting the above technical scheme, river sand, rosin resin, and expanded graphite grafted polyamide resin are matched, and the good strength and toughness of polyamide resin are utilized to improve the mechanical strength of the finished concrete; the bonding effect of polyamide resin and cementitious materials is utilized. After a fire occurs, even if water in the cementitious material is lost and cracks are generated, the expansion effect of expanded graphite can be used to fill the pores, and the bonding effect of polyamide resin after hot melting is combined to ensure that polyamide resin-modified sand and polyetheretherketone-modified crushed stone, high-strength fiber, and high-strength filler are bonded to each other during the fire. By filling the cracks and pores and combining with the good bonding effect, the fire can be avoided as much as possible to avoid a sharp decrease in concrete strength, thereby minimizing the collapse of the concrete.

[0017] Preferably, the expanded graphite grafted polyamide resin is made of polyamide resin, expanded graphite and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.3:0.1-0.2.

[0018] By adopting the above technical scheme, polyamide resin, expanded graphite and polyvinyl alcohol solution are matched, and the bonding effect of the polyvinyl alcohol solution is utilized to facilitate bonding of the expanded graphite to the polyamide resin, and the hydroxyl groups in the polyvinyl alcohol are cross-linked and bonded with the cementitious material and the polyetheretherketone modified crushed stone, thereby improving the structural strength of the concrete; and the expanded graphite is more stably bonded in the concrete. After a fire occurs, the expansion effect of the expanded graphite combined with the hot-melt viscosity of the polyamide resin can fill and bond cracks to ensure the strength of the concrete after the fire.

[0019] Preferably, the high-strength fiber is composed of basalt fiber, waterproof asbestos fiber and polyimide modified aramid fiber in a mass ratio of 1:0.5-1:0.5-1.

[0020] By adopting the above technical scheme, basalt fiber, hydrophobic asbestos fiber, and polyimide modified aramid fiber are matched, and the filling and connecting effect of basalt fiber and its high strength are utilized to improve the strength of concrete; the flame retardant effect of high-strength concrete is improved by combining the good heat resistance and heat insulation effect of asbestos fiber in hydrophobic asbestos fiber, and the asbestos fiber has good flexibility and can be bent and folded in the internal structure of concrete, and can buffer when migration force or impact force occurs, thereby avoiding the generation of cracks in the concrete as much as possible; at the same time, combined with the high strength of aramid fiber and the toughness of polyimide, the strength and impact resistance of concrete are further improved. When a fire occurs, the bonding effect of polyimide can be used to further improve the bonding effect between the fiber and other materials, thereby ensuring that the concrete has a high strength after the fire, and it is not easy to cause the problem of high-rise building collapse due to excessive cracks.

[0021] Preferably, the waterproof asbestos fiber is made of asbestos fiber and ethyl cellulose solution in a mass ratio of 1:0.2-0.5.

[0022] By adopting the above technical solution, asbestos fibers and ethyl cellulose solution are combined, and the water insolubility of ethyl cellulose is utilized to ensure the hydrophobic effect of asbestos fibers, and to avoid asbestos absorbing mixing water and affecting the hydration effect of concrete, thereby ensuring that the concrete has a higher strength.

[0023] After a fire occurs, the flame retardancy of concrete can be improved by utilizing the better flame retardant and heat insulating effect of asbestos fiber and the carbonization flame retardant effect of ethyl cellulose, thereby protecting the strength of concrete and reducing the strength loss value of concrete.

[0024] Preferably, the polyimide-modified aramid fiber is prepared from aramid fiber, polyimide and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.2:0.05-0.1.

[0025] By adopting the above technical scheme, aramid fiber and polyimide are combined, and the higher strength of aramid fiber is combined with the flame retardant effect of aramid fiber and polyimide to improve the fire retardancy of concrete; and after the polyimide is hot-melted in a fire, the bonding effect between the fiber and the cementitious material, polyetheretherketone modified gravel, and polyamide resin modified sand can be improved, so as to avoid the problem of cracking and causing the collapse of the concrete.

[0026] Preferably, the high-strength filler is composed of quartz stone, aluminum hydroxide, zinc borate and silicon boride in a mass ratio of 1:0.5-1:0.1-0.2:0.1-0.2.

[0027] By adopting the above technical scheme, quartz stone, aluminum hydroxide, zinc borate and silicon boride are matched, and the higher strength of quartz stone and silicon boride is used to improve the strength of concrete, and the flame retardant effect of aluminum hydroxide, zinc borate and silicon boride is used to improve the fire retardancy of concrete; and silicon boride is resistant to low temperatures and is not prone to bursting during the alternating process of hot and cold, thereby avoiding cracks inside the concrete as much as possible to ensure the strength of the concrete.

[0028] In a second aspect, the present application provides a method for preparing high-strength wear-resistant concrete, which adopts the following technical solution: A method for preparing high-strength wear-resistant concrete comprises the following steps: S1, weigh cement, fly ash, and mineral powder, mix and stir evenly, then add polyetheretherketone modified gravel and polyamide resin modified sand, mix and stir evenly to obtain a primary mixture; S2, adding high-strength fiber and high-strength filler to the primary mixture and mixing evenly, and then adding water reducing agent and water and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain a finished product.

[0029] By adopting the above technical solution, the finished concrete has higher strength and better fire retardancy. After a fire occurs, the concrete of the high-rise building still has higher structural stability and strength, and is not prone to collapse due to high-temperature cracking and cracks caused by low-temperature fire extinguishing, thus buying time for fire rescue and personnel evacuation.

[0030] In summary, this application has the following beneficial effects: 1. The combination of polyetheretherketone modified gravel, polyamide resin modified sand, high-strength fiber and high-strength filler utilizes the higher strength of polyetheretherketone and polyamide resin combined with the strength of high-strength fiber and high-strength filler to improve the strength and wear resistance of concrete; the high-temperature viscosity of polyetheretherketone and the high-temperature bonding effect of polyamide resin are utilized to ensure that the concrete of high-rise buildings is not prone to cracking under high-temperature fire, ensure the structural strength of concrete, and buy more time for personnel evacuation and rescue.

[0031] 2. The combination of polyetheretherketone modified gravel and polyamide resin modified sand utilizes the flexibility of polyetheretherketone and polyamide resin to improve the strength and impact resistance of concrete, and make the concrete less likely to crack. After a fire occurs, the flame retardant effect of calcium phosphate aluminate and the carbonization flame retardant effect of sodium alginate, combined with the high-temperature hot-melt adhesiveness of polyetheretherketone and polyamide resin, can bond the gravel with sand, high-strength fiber, high-strength filler, and cementitious material, so that the high-strength concrete has better fire resistance and flame retardancy, and can also ensure the strength of the high-strength concrete, so that the high-strength concrete of high-rise buildings is not prone to large cracks and collapse in a fire.

[0032] 3. The combination of rosin resin and calcium phosphate aluminate grafted polyetheretherketone and the use of hot-melt rosin resin can further improve the bonding effect between crushed stone and cementitious materials and other materials, and improve the strength of concrete. During a fire, the rosin resin melts, further improving the bonding stability between crushed stone and other materials and avoiding the generation of cracks as much as possible. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] The following raw materials are all commercially available.

[0035] Preparation example of polyetheretherketone modified gravel Preparation Example 1: Polyetheretherketone modified gravel is prepared by the following method: 0.15 kg of sodium alginate solution is uniformly sprayed on the surface of 1 kg of polyetheretherketone, the average particle size of the polyetheretherketone is 50 μm, and the sodium alginate solution is a sodium alginate aqueous solution with a mass fraction of 1%, to obtain pretreated polyetheretherketone; then 0.3 kg of calcium phosphate aluminate is added, the average particle size of the calcium phosphate aluminate is 20 μm, the addition rate of the calcium phosphate aluminate is 60 g / min, and the stirring rate of the pretreated polyetheretherketone during the addition process is 100 r / min. After uniform mixing, the mixture is dried and dispersed to obtain calcium phosphate aluminate grafted polyetheretherketone, and the calcium phosphate aluminate polyetheretherketone is sieved through a 150-mesh sieve; 1000kg of crushed stone, 4kg of rosin resin and 10kg of calcium phosphate-grafted polyetheretherketone are mixed and stirred evenly. The crushed stone is a continuously graded crushed stone particle with a particle size of 5-20mm. The temperature is raised to 175℃ and the mixing and stirring is continued for 2 minutes. The rosin resin is hot-melted. After mixing evenly, it is dried and dispersed until the crushed stone particles do not stick to each other and agglomerate to obtain the finished polyetheretherketone modified crushed stone.

[0036] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.1 kg of sodium alginate solution is uniformly sprayed on the surface of 1 kg of polyetheretherketone, the average particle size of the polyetheretherketone is 50 μm, and the sodium alginate solution is a sodium alginate aqueous solution with a mass fraction of 1%, to obtain pretreated polyetheretherketone; then 0.2 kg of calcium phosphate aluminate is added, the average particle size of the calcium phosphate aluminate is 20 μm, the addition speed of the calcium phosphate aluminate is 60 g / min, and the stirring speed of the pretreated polyetheretherketone during the addition process is 100 r / min. After uniform mixing, the mixture is dried and dispersed to obtain calcium phosphate aluminate grafted polyetheretherketone, and the calcium phosphate aluminate polyetheretherketone is sieved through a 150-mesh sieve; 1000kg of crushed stone, 2kg of rosin resin and 5kg of calcium phosphate-grafted polyetheretherketone are mixed and stirred evenly. The crushed stone is a continuously graded crushed stone particle with a particle size of 5-20mm. The temperature is raised to 175℃ and the mixing and stirring is continued for 2 minutes. The rosin resin is hot-melted. After mixing evenly, it is dried and dispersed until the crushed stone particles do not stick to each other and agglomerate to obtain the finished product of polyetheretherketone modified crushed stone.

[0037] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.2 kg of sodium alginate solution is uniformly sprayed on the surface of 1 kg of polyetheretherketone, the average particle size of the polyetheretherketone is 50 μm, and the sodium alginate solution is a sodium alginate aqueous solution with a mass fraction of 1%, to obtain pretreated polyetheretherketone; then 0.4 kg of calcium phosphate aluminate is added, the average particle size of the calcium phosphate aluminate is 20 μm, the addition speed of the calcium phosphate aluminate is 60 g / min, and the stirring speed of the pretreated polyetheretherketone during the addition process is 100 r / min. After uniform mixing, the mixture is dried and dispersed to obtain calcium phosphate aluminate grafted polyetheretherketone, and the calcium phosphate aluminate polyetheretherketone is sieved through a 150-mesh sieve; 1000kg of crushed stone, 5kg of rosin resin and 15kg of calcium phosphate-grafted polyetheretherketone are mixed and stirred evenly. The crushed stone is a continuously graded crushed stone particle with a particle size of 5-20mm. The temperature is raised to 175℃ and the mixing and stirring is continued for 2 minutes. The rosin resin is hot-melted. After mixing evenly, it is dried and dispersed until the crushed stone particles do not stick to each other and agglomerate to obtain the finished polyetheretherketone modified crushed stone.

[0038] Preparation example of polyamide resin modified sand Preparation Example 4: Polyamide resin modified sand is prepared by the following method: 0.15 kg of polyvinyl alcohol solution is uniformly sprayed on the surface of 1 kg of polyamide resin, the average particle size of the polyamide resin is 50 μm, and the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 1%, so as to obtain a pretreated polyamide resin; then 0.2 kg of expanded graphite is added, the average particle size of the expanded graphite is 5 μm, and the adding speed of the expanded graphite is 30 g / min. During the adding process, the pretreated polyamide resin is stirred at a speed of 100 r / min, and after being uniformly mixed, it is dried and dispersed to obtain an expanded graphite grafted polyamide resin; the expanded graphite grafted polyamide resin is sieved through a 200 mesh sieve; 1000kg river sand, 2kg rosin resin and 5kg expanded graphite grafted polyamide resin were mixed and stirred evenly. The sand was medium sand in zone II, and the apparent density was 2660kg / m 3 , fineness modulus is 2.5, mud content is <1.0%, temperature is raised to 175℃ and mixing and stirring is continued for 2 minutes, rosin resin is hot-melted, mixed evenly, dried and dispersed until river sand particles do not stick to each other and agglomerate, and the finished polyamide resin modified sand is obtained.

[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 0.1 kg of polyvinyl alcohol solution is uniformly sprayed on the surface of 1 kg of polyamide resin, the average particle size of the polyamide resin is 50 μm, and the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 1%, so as to obtain a pretreated polyamide resin; then 0.1 kg of expanded graphite is added, the average particle size of the expanded graphite is 5 μm, and the adding speed of the expanded graphite is 30 g / min. During the adding process, the pretreated polyamide resin is stirred at a speed of 100 r / min, and after being uniformly mixed, it is dried and dispersed to obtain an expanded graphite grafted polyamide resin; 1000kg of river sand, 1kg of rosin resin and 3kg of expanded graphite grafted polyamide resin were mixed and stirred evenly, and the temperature was raised to 175°C and the mixing and stirring was continued for 2 minutes. The rosin resin was hot-melted. After mixing evenly, it was dried and dispersed until the river sand particles did not stick to each other and agglomerated, and the finished polyamide resin modified sand was obtained.

[0040] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 0.2 kg of polyvinyl alcohol solution is uniformly sprayed on the surface of 1 kg of polyamide resin, the average particle size of the polyamide resin is 50 μm, and the polyvinyl alcohol solution is a polyvinyl alcohol aqueous solution with a mass fraction of 1%, so as to obtain a pretreated polyamide resin; then 0.3 kg of expanded graphite is added, the average particle size of the expanded graphite is 5 μm, and the adding speed of the expanded graphite is 30 g / min. During the adding process, the pretreated polyamide resin is stirred at a speed of 100 r / min, and after being uniformly mixed, it is dried and dispersed to obtain an expanded graphite grafted polyamide resin; 1000kg of river sand, 3kg of rosin resin and 8kg of expanded graphite grafted polyamide resin were mixed and stirred evenly, and the temperature was raised to 175°C and the mixing and stirring was continued for 2 minutes. The rosin resin was hot-melted. After mixing evenly, it was dried and dispersed until the river sand particles did not stick to each other and agglomerated, and the finished polyamide resin modified sand was obtained.

[0041] Preparation example of waterproof asbestos fiber Preparation Example 7: Waterproof asbestos fiber is prepared by the following method: 0.4 kg of ethyl cellulose solution was uniformly sprayed on the surface of 1 kg of asbestos fiber, the average length of the asbestos fiber was 3 mm, and the ethyl cellulose solution was 1% by mass of ethyl cellulose ethanol solution. The finished waterproof asbestos fiber was obtained by drying and dispersing until the asbestos fibers did not stick to each other and agglomerate.

[0042] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 0.2 kg of ethyl cellulose solution is evenly sprayed on the surface of 1 kg of asbestos fiber, the average length of the asbestos fiber is 3 mm, and the ethyl cellulose solution is a 1% by mass ethyl cellulose ethanol solution. The finished waterproof asbestos fiber is obtained by drying and dispersing until the asbestos fibers do not stick to each other and agglomerate.

[0043] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 0.5 kg of ethyl cellulose solution is evenly sprayed on the surface of 1 kg of asbestos fiber, the average length of the asbestos fiber is 3 mm, and the ethyl cellulose solution is a 1% by mass ethyl cellulose ethanol solution. The finished waterproof asbestos fiber is obtained by drying and dispersing until the asbestos fibers do not stick to each other and agglomerate.

[0044] Preparation example of polyimide modified aramid fiber Preparation Example 10: Polyimide modified aramid fiber is prepared by the following method: 0.08 kg of polyvinyl alcohol solution was uniformly sprayed on the surface of 1 kg of aramid fiber, the average length of the aramid fiber was 2 mm, and the polyvinyl alcohol solution was a polyvinyl alcohol aqueous solution with a mass fraction of 1%. Then 0.15 kg of polyimide was added, the average particle size of the polyimide was 20 μm, and the addition rate of the polyimide was 60 g / min. During the adding process, the aramid fiber was stirred at a speed of 100 r / min. After being evenly mixed, it was dried and dispersed until the aramid fibers did not stick to each other and agglomerated to obtain a finished product.

[0045] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 0.05 kg of polyvinyl alcohol solution was evenly sprayed on the surface of 1 kg of aramid fiber, the average length of the aramid fiber was 2 mm, and the polyvinyl alcohol solution was a polyvinyl alcohol aqueous solution with a mass fraction of 1%. Then 0.1 kg of polyimide was added, the average particle size of the polyimide was 20 μm, and the addition rate of the polyimide was 60 g / min. During the adding process, the aramid fiber was stirred at a speed of 100 r / min. After being evenly mixed, it was dried and dispersed until the aramid fibers did not stick to each other and agglomerated to obtain a finished product.

[0046] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 0.1 kg of polyvinyl alcohol solution was evenly sprayed on the surface of 1 kg of aramid fiber, the average length of the aramid fiber was 2 mm, the polyvinyl alcohol solution was a polyvinyl alcohol aqueous solution with a mass fraction of 1%, and then 0.2 kg of polyimide was added, the average particle size of the polyimide was 20 μm, and the addition rate of the polyimide was 60 g / min. During the adding process, the aramid fiber was stirred at a speed of 100 r / min. After being evenly mixed, it was dried and dispersed until the aramid fibers did not stick to each other and agglomerated to obtain a finished product. Example

[0047] Example 1: A high-strength wear-resistant concrete: 400kg cement, 165kg water, 70kg fly ash, 130kg mineral powder, 1000kg polyetheretherketone modified crushed stone, 750kg polyamide resin modified sand, 3kg water reducer, 25kg high-strength fiber, 30kg high-strength filler; cement is silicate cement with a P.O42.5; fly ash is Class F II fly ash, with a fineness of 8% (45μm square hole sieve residue), loss on ignition <4.5%, water requirement ratio <96%, and water content <0.2%; mineral powder is S95 grade slag powder with a density of 2.8g / cm 3 , with a specific surface area of ​​420m 2 / kg, activity index (7d) is 82%, activity index (28d) is 94%, fluidity ratio is 96%, water content is 0.2%; water reducer is polycarboxylic acid high-efficiency water reducer; polyetheretherketone modified gravel is selected from the polyetheretherketone modified gravel prepared in Preparation Example 1; polyamide resin modified sand is selected from the polyamide resin modified sand prepared in Preparation Example 4; high-strength fiber is composed of basalt fiber, waterproof asbestos fiber prepared in Preparation Example 7 and polyimide modified aramid fiber prepared in Preparation Example 10 in a mass ratio of 1:1:1, and the average length of basalt fiber is 3mm; high-strength filler is composed of quartz stone, aluminum hydroxide, zinc borate and silicon boride in a mass ratio of 1:0.7:0.15:0.15, the average particle size of quartz stone is 100μm, the average particle size of silicon boride is 20μm, the average particle size of aluminum hydroxide is 80μm, and the average particle size of zinc borate is 80μm; The preparation method is as follows: S1, weigh cement, fly ash, and mineral powder, mix and stir evenly, then add polyetheretherketone modified gravel and polyamide resin modified sand, mix and stir evenly to obtain a primary mixture; S2, adding high-strength fiber and high-strength filler to the primary mixture and mixing evenly, and then adding water reducing agent and water and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain a finished product.

[0048] Embodiment 2: This embodiment differs from Embodiment 1 in that: 350kg cement, 150kg water, 50kg fly ash, 120kg mineral powder, 950kg polyetheretherketone modified gravel, 600kg polyamide resin modified sand, 2kg water reducer, 20kg high-strength fiber, 25kg high-strength filler; the polyetheretherketone modified gravel is the polyetheretherketone modified gravel prepared in Preparation Example 2; the polyamide resin modified sand is the polyamide resin modified sand prepared in Preparation Example 5; the high-strength fiber is composed of basalt fiber in a mass ratio of 1:0.5:0.5, waterproof asbestos fiber prepared in Preparation Example 8 and polyimide modified aramid fiber prepared in Preparation Example 11; the high-strength filler is composed of quartz stone, aluminum hydroxide, zinc borate and silicon boride in a mass ratio of 1:0.5:0.1:0.1.

[0049] Embodiment 3: This embodiment differs from Embodiment 1 in that: 450kg cement, 180kg water, 80kg fly ash, 140kg mineral powder, 1100kg polyetheretherketone modified gravel, 900kg polyamide resin modified sand, 4kg water reducer, 30kg high-strength fiber, 35kg high-strength filler; the polyetheretherketone modified gravel is the polyetheretherketone modified gravel prepared in Preparation Example 3; the polyamide resin modified sand is the polyamide resin modified sand prepared in Preparation Example 6; the high-strength fiber is composed of basalt fiber in a mass ratio of 1:1:1, waterproof asbestos fiber prepared in Preparation Example 9 and polyimide modified aramid fiber prepared in Preparation Example 12; the high-strength filler is composed of quartz stone, aluminum hydroxide, zinc borate and silicon boride in a mass ratio of 1:1:0.2:0.2.

[0050] Embodiment 4: This embodiment differs from Embodiment 1 in that: In the preparation process of polyetheretherketone modified gravel, polyetheretherketone grafted with calcium phosphate was replaced by polyetheretherketone particles of equal mass.

[0051] Embodiment 5: This embodiment differs from Embodiment 1 in that: In the preparation process of polyamide resin modified sand, calcium aluminophosphate is replaced by calcium carbonate of equal mass.

[0052] Embodiment 6: This embodiment differs from Embodiment 1 in that: In the preparation process of polyamide resin modified sand, the expanded graphite grafted polyamide resin is replaced by polyamide resin of equal mass.

[0053] Embodiment 7: This embodiment differs from Embodiment 1 in that: In the preparation process of polyamide resin modified sand, the expanded graphite is replaced by an equal mass of silicon dioxide.

[0054] Embodiment 8: This embodiment differs from Embodiment 1 in that: The waterproof asbestos fiber is replaced by asbestos fiber of equal quality in high-strength fiber.

[0055] Embodiment 9: This embodiment differs from Embodiment 1 in that: In high-strength fibers, aramid fibers of equal quality are used to replace polyimide-modified aramid fibers.

[0056] Embodiment 10: This embodiment differs from Embodiment 1 in that: Aluminum hydroxide, zinc borate and silicon boride are not added to the high-strength filler.

[0057] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The raw materials are replaced with crushed stones of equal mass for the polyetheretherketone modified crushed stones.

[0058] Comparative Example 2: The difference between this comparative example and Example 1 is that: The polyamide resin modified sand is replaced by river sand of equal quality in the raw materials.

[0059] Performance testing 1. Compressive strength test Finished concrete was prepared by the preparation methods of Examples 1-10 and Comparative Examples 1-2, and the compressive strength was tested with reference to GB / T 50081-2019 Concrete Physical and Mechanical Properties Test Method Standard, and the data for 28 days was recorded.

[0060] 2. Wear resistance test The finished concrete specimens were prepared by the preparation method of Examples 1-3. The specimens were cylindrical and had a diameter of 23 mm and a height of 60 mm. Test principle: the specimens were placed on the fixture of the testing machine, and a certain load was applied to the specimens. Then the grinding disc rotated uniformly around the central axis at a certain speed, driving the abrasive thereon to rub the surface of the specimens. The wear value per unit area of ​​the specimens was calculated as an evaluation index of the wear resistance of the concrete.

[0061] Main parameters: Grinding disc diameter: 52.5cm; Grinding disc speed 32r / min; Test load: provided by weight, load 4.1kg; Test abrasive: Brown corundum with a particle size of 0.5mm is used, and the abrasive can be reused 3 times; Test speed: Before the test, grind the specimen for 30 turns to remove the surface slurry, and then grind it for 100 turns.

[0062] Test steps: 1) Measure the diameter of each specimen to an accuracy of 0.05 mm, and take the arithmetic mean of three measurement results at different locations as the final measurement result; 2) Grind the specimen for 30 turns to remove the surface slurry, then clean, dry (dry in an oven at about 40°C for 0.5h) and weigh the specimen (G1); 3) Place two test pieces in the fixture, add weights, start the motor, rotate the grinding disc at a speed of 32r / min, and then adjust the throttle valve to make the abrasive fall evenly from the funnel to the grinding disc at a speed of 0.5L / min. During the grinding process, the test piece is fixed in the fixture, the test piece does not move, and the grinding disc rotates, driving the abrasive on the grinding disc to grind the test piece; 4) When the grinding speed reaches 100, turn off the motor, remove the test piece, clean and dry (dry in an oven at about 40°C for 0.5h) the test piece and weigh it (G2).

[0063] Test result calculation: Formula: R = (G1-G2) / A Where: R—abrasion value, g / cm 2 ; G1—mass of specimen before grinding, g; G2—mass of specimen after grinding, g; A—grinding area of ​​specimen, cm 2 .

[0064] 3. Fire resistance test The finished concrete was prepared by the preparation method of Examples 1-10 and Comparative Examples 1-2, first burned at 400°C for 3 minutes, then burned at 800°C for 10 minutes, and then burned at 300°C for 5 minutes, simulating the temperature of initial fire heating, high-temperature combustion, and fire extinguishing and cooling. The GB / T 50081-2019 concrete physical and mechanical properties test method standard was referred again to test the compressive strength and record the data. When the concrete of a high-rise building caught fire, although the temperature at the fire location was high, the temperature around the fire did not reach the temperature of the maximum fire, and the simulated temperature was feasible.

[0065] 4. Crack resistance test Finished concrete was prepared by the preparation methods of Examples 1-10 and Comparative Examples 1-2. Standard test blocks were prepared with reference to the method of GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the number of cracks after concrete pouring for 24 hours was calculated; the concrete was first burned at 400°C for 3 minutes, then at 800°C for 10 minutes, and then at 300°C for 5 minutes to simulate the temperature of initial fire heating, high-temperature combustion, and fire extinguishing and cooling; the number of cracks was then recorded again, and the data was recorded; the concrete sample size was 100cm×100cm×10cm.

[0066] Table 1 Performance test table It can be seen from Examples 1-3 and Table 1 that the concrete prepared in the present application has the advantages of high strength, good wear resistance, still having high strength after fire, fewer cracks, and higher stability.

[0067] Combining Example 1 and Examples 4-10 and Table 1, it can be seen that in the preparation process of polyetheretherketone modified gravel in Example 4, calcium phosphate aluminate grafted polyetheretherketone is replaced with polyetheretherketone particles of equal mass, and in the preparation process of polyamide resin modified sand in Example 5, calcium phosphate aluminate is replaced with calcium carbonate of equal mass. Compared with Example 1, the compressive strength of concrete prepared in Examples 4 and 5 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after the fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; this indicates that polyetheretherketone, calcium phosphate aluminate and sodium alginate solution are combined, and polyetheretherketone has good flexibility and can ensure the strength of concrete. During the fire, the hot melt adhesiveness of polyetheretherketone is combined with the flame retardant effect of calcium phosphate aluminate to bond the gravel to other raw materials, so as to avoid serious loss of concrete strength and the appearance of large cracks after the fire, so that the concrete is not prone to collapse.

[0068] In the preparation process of polyamide resin modified sand in Example 6, the expanded graphite grafted polyamide resin is replaced by polyamide resin of equal mass. In the preparation process of polyamide resin modified sand in Example 7, the expanded graphite is replaced by silicon dioxide of equal mass. Compared with Example 1, the compressive strength of concrete prepared in Examples 6 and 7 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after the fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; this indicates that polyamide resin has higher strength and better toughness and can improve the strength of concrete. During the fire, the viscosity of polyamide resin and the expansion effect of expanded graphite can fill the pores, so that the polyamide resin modified sand and polyetheretherketone modified crushed stone, high-strength fiber and high-strength filler are bonded to each other. By filling the cracks and pores and cooperating with better bonding effect, the fire can be avoided to avoid a sharp decrease in concrete strength, thereby avoiding the collapse of concrete as much as possible.

[0069] In Example 8, the waterproof asbestos fiber is replaced by asbestos fiber of equal quality in the high-strength fiber. Compared with Example 1, the compressive strength of the concrete prepared in Example 8 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after the fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; this indicates that asbestos fibers that have not been hydrophobically treated easily absorb water and affect the hydration effect of cement, thereby affecting the strength of the concrete, while ethyl cellulose has a carbonization flame retardant effect, which can further improve the fire retardancy of the concrete, ensure that the concrete has a certain strength after a fire, and is not prone to collapse.

[0070] In Example 9, aramid fibers of equal mass are used to replace polyimide-modified aramid fibers in the high-strength fibers. Compared with Example 1, the compressive strength of concrete prepared in Example 9 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; this indicates that aramid fibers and polyimide are combined to improve the fire retardancy of concrete by utilizing the higher strength of aramid fibers and the flame retardant effects of aramid fibers and polyimide; and after hot melting in a fire, polyimide can improve the bonding effect between fibers and cementitious materials, polyetheretherketone modified gravel, and polyamide resin modified sand, thereby minimizing the problem of concrete collapse caused by cracking.

[0071] In Example 10, no aluminum hydroxide, zinc borate and silicon boride are added to the high-strength filler. Compared with Example 1, the compressive strength of the concrete prepared in Example 10 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; this indicates that the higher strength of quartz stone and silicon boride improves the strength of concrete, and the flame retardant effect of aluminum hydroxide, zinc borate and silicon boride is utilized to improve the fire retardancy of concrete; and silicon boride is resistant to low temperatures, and is not prone to bursting during the alternating process of hot and cold, thereby avoiding cracks inside the concrete as much as possible to ensure the strength of the concrete.

[0072] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that the raw materials of Comparative Example 1 are replaced with polyetheretherketone modified gravel with the same mass of gravel, and the raw materials of Comparative Example 2 are replaced with the same mass of river sand. The polyamide resin modified sand is compared with Example 1. The compressive strength of the concrete prepared in Comparative Examples 1 and 2 is lower than that in Example 1, the difference between the initial compressive strength and the compressive strength after the fire is greater than the corresponding difference in Example 1, and the number of cracks is greater than that in Example 1; This indicates that the polyetheretherketone modified gravel, polyamide resin modified sand, high-strength fiber, and high-strength filler are matched, and the higher strength of polyetheretherketone and polyamide resin is combined with the strength of high-strength fiber and high-strength filler to improve the strength and wear resistance of the concrete; and the concrete still has good stability and high strength after the fire to meet the use of high-rise buildings.

[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength wear-resistant concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 350-450 parts of cement, 150-180 parts of water, 50-80 parts of fly ash, 120-140 parts of mineral powder, 950-1100 parts of polyetheretherketone modified gravel, 600-900 parts of polyamide resin modified sand, 2-4 parts of water reducing agent, 20-30 parts of high-strength fiber and 25-35 parts of high-strength filler.

2. The high-strength wear-resistant concrete according to claim 1, characterized in that: The polyetheretherketone modified crushed stone is made of crushed stone, rosin resin and calcium phosphate-grafted polyetheretherketone in a mass ratio of 1000:2-5:5-15.

3. The high-strength wear-resistant concrete according to claim 2, characterized in that: The calcium aluminophosphate grafted polyetheretherketone is prepared from polyetheretherketone, calcium aluminophosphate and sodium alginate solution in a mass ratio of 1:0.2-0.4:0.1-0.

2.

4. The high-strength wear-resistant concrete according to claim 1, characterized in that: The polyamide resin modified sand is made of river sand, rosin resin and expanded graphite grafted polyamide resin in a mass ratio of 1000:1-3:3-8.

5. The high-strength wear-resistant concrete according to claim 4, characterized in that: The expanded graphite grafted polyamide resin is prepared from polyamide resin, expanded graphite and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.3:0.1-0.

2.

6. The high-strength wear-resistant concrete according to claim 1, characterized in that: The high-strength fiber is composed of basalt fiber, waterproof asbestos fiber and polyimide modified aramid fiber in a mass ratio of 1:0.5-1:0.5-1.

7. The high-strength wear-resistant concrete according to claim 6, characterized in that: The waterproof asbestos fiber is prepared from asbestos fiber and ethyl cellulose solution in a mass ratio of 1:0.2-0.

5.

8. The high-strength wear-resistant concrete according to claim 6, characterized in that: The polyimide-modified aramid fiber is prepared from aramid fiber, polyimide and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.2:0.05-0.

1.

9. The high-strength wear-resistant concrete according to claim 1, characterized in that: The high-strength filler is composed of quartz stone, aluminum hydroxide, zinc borate and silicon boride in a mass ratio of 1:0.5-1:0.1-0.2:0.1-0.

2.

10. The method for preparing high-strength wear-resistant concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, weigh cement, fly ash, and mineral powder, mix and stir evenly, then add polyetheretherketone modified gravel and polyamide resin modified sand, mix and stir evenly to obtain a primary mixture; S2, adding high-strength fiber and high-strength filler to the primary mixture and mixing evenly, and then adding water reducing agent and water and mixing evenly to obtain a mixture; S3. The mixture is poured and cured to obtain a finished product.